2022
DOI: 10.12688/f1000research.75364.1
|View full text |Cite
|
Sign up to set email alerts
|

What can we experience and report on a rapidly presented image? Intersubjective measures of specificity of freely reported contents of consciousness

Abstract: Background: A majority of previous studies appear to support a view that human observers can only perceive coarse information from a natural scene image when it is presented rapidly (<100ms, masked). In these studies, participants were often forced to choose an answer from options that experimenters preselected. These options can underestimate what participants experience and can report on it. The current study aims to introduce a novel methodology to investigate how detailed information participants can re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…This was despite the fact that we ran the experiment online, where one might expect the performance may not be as good as for in-laboratory participants. Along with previous psychophysics studies [ 35 , 39 41 ], we found that was not the case. We first considered the possibility that Experiment 1 participants showed worse performance because of memory decay (20 probes in Experiment 1 versus 6 probes in Experiment 2, after each image) or fatigue (2 h in Experiment 1 versus 30 min in Experiment 2).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This was despite the fact that we ran the experiment online, where one might expect the performance may not be as good as for in-laboratory participants. Along with previous psychophysics studies [ 35 , 39 41 ], we found that was not the case. We first considered the possibility that Experiment 1 participants showed worse performance because of memory decay (20 probes in Experiment 1 versus 6 probes in Experiment 2, after each image) or fatigue (2 h in Experiment 1 versus 30 min in Experiment 2).…”
Section: Resultssupporting
confidence: 83%
“…For efficient data collection (and in part due to COVID restriction in face-to-face experiments), we performed Experiment 2 online. In our experience, online experiments work better by shortening the task, unlike two one-hour sessions as in Experiment 1 [ 35 ]. Given this, we proposed Experiment 2 to collect the data from 240 participants (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…As another possible empirical experiment, we can propose "reconstruction" experiments using natural images 11 . For example, an array of natural images can be briefly presented to participants asking them what they saw in the image (Chuyin et al, 2022;Qianchen et al, 2022). In other words, this task is considered as a functor Report with conscious experiences as objects in Q and reports as objects in B.…”
Section: Conceptual Clarificationmentioning
confidence: 99%
“…In other words, this task is considered as a functor Report with conscious experiences as objects in Q and reports as objects in B. Participants can freely report what they saw by typing words (Chuyin et al, 2022). Or they can express whether they saw a patch of an image in the target image or not (Qianchen et al, 2022).…”
Section: Conceptual Clarificationmentioning
confidence: 99%
“…This requirement cannot be characterised in terms of stimulus energy, because the system may be differentially sensitive to attributes that are distinguished by stimulus configuration rather than physical amplitude (3)(4)(5). Observers are able to extract large amounts of information from brief displays, and certain types of information are perceived more readily than others (4)(5)(6)(7)(8), suggesting that visual pathways are calibratedperhaps by the top-down influence of pre-existing internal models (9) -to prioritise certain stimulus properties for processing. The more attuned the system is to a visual feature, the less exposure to this feature should be required to process it.…”
mentioning
confidence: 99%